PREVENTION OF REVERSE IGNITION IN CAR ENGINES - Nasirov Ilham Zakirovich; Rakhmonov Khurshidbek Nurmuhammad oghli (Scholar Express Journal, 2022)
Engines with spark ignition have external and internal methods of mixture formation. The engine of the car "Tico" with external mixture formation was tested on the stand. Infrequent backfires in the air filter housing were observed when starting and restarting the engine. The engine of the Nexia car with internal mixture formation was tested at the stand. There were no backfires during start-up, restart and in all operating modes of this engine.
Keywords: Car; engine; fuel; complete